PENGARUH PERSEPSI HARGA, PROMOSI DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN: (Studi pada Konsumen Kopi Kenangan Ruko Puri Beta di Tangerang) - Syafika Rasya Augustin; Ravindra Safitra Hidayat (Jurnal Ilmiah Manajemen dan Akuntansi, 2024)
One of the businesses that is growing today is the culinary field, which includes food and beverages, such as Kopi Kenangan. The purpose of this study is to determine the influence of price perception, promotion and location on consumer purchase decisions of Kopi Kenangan Ruko Puri Beta in Tangerang. The population in this study is consumers of Kopi Kenangan Ruko Puri Beta in Tangerang. The sample in this study amounted to 96 respondents. In this study, the sampling technique used by the author is the Non Probability Sampling technique using the purposive sampling technique approach. The analysis tool used is SPSS 26. The results of the study were that the price perception, promotion and location had a significant effect on the purchase decision of consumers of Kopi Kenangan Ruko Puri Beta in Tangerang.